Effects of high-intensity running training on soccer-specific fitness in professional male player - Wells, C.; Edwards, A.; Fysh, M.; Drust, B. (Applied Physiology, Nutrition, and Metabolism, 2014)
The purpose of this study was to investigate whether or not physiological and performance gains could be achieved with the addition of high-intensity running to an existing training programme in a group of well trained professional male soccer players. Sixteen professional male players (21.3 ± 2.1 years, stature 177.4 ± 4.2 cm, body mass 73.1 ± 8.1 kg) were randomised in training (TRA, n = 8) and control (CON, n = 8) groups. All players performed physiological assessments before and after a 6-week intervention. Outcome measures were: (i) VO2peak, (ii) VO2 kinetics during very heavy-intensity exercise, (iii) a maximal anaerobic running test, and (iv) Yo-Yo Intermittent Recovery Test level 2 (YIRT2). The only aerobic parameter to change after the intervention was the phase III time constant at exercise onset for CON, which lengthened (p = 0.012) to a value similar to that of the TRA group. However, TRA showed gains in anaerobic performance (p = 0.021), time to exhaustion (p = 0.019), and maximal running speed (p = 0.023). In the YIRT2, distance run increased for TRA over time (p = 0.015), and the TRA group were also capable of running further in the YIRT2 after the intervention compared with CON (p = 0.011). This study shows it is possible to improve the soccer-specific high-intensity running capacity of professional players when high-intensity intermittent training is added to the normal training load and that this effect is only detectable in anaerobic capabilities. The observed effects are meaningful to the training practices of elite athletes seeking a competitive edge in team sports when otherwise well matched.